Metatranscriptomic Analysis of Corals Inoculated With Tolerant and Non-Tolerant Symbiont Exposed to High Temperature and Light Stress - Yuyama, Ikuko; Higuchi, Tomihiko; Mezaki, Takuma; Tashiro, Hisako; Ikeo, Kazuho (Frontiers in Physiology, 2022)
Algal symbionts of corals can influence host stress resistance; for example, whereas Cladocopium (C-type) is generally dominant in corals, Durusdinium (D-type) is found in more heat-resistant corals. Thus, the presence of D-type symbiont likely increases coral heat tolerance, and this symbiotic relationship potentially provides a hint to increasing the stress tolerance of coral–algal symbioses. In this study, transcriptome profiles of Cladocopium- and Durusdinium-harboring Acrioira solitaryensis (C-coral and D-coral, respectively), and algal chlorophyll parameter (Fv/Fm) under bleaching conditions (high temperature and light stress) were compared. Stress treatment caused coral bleaching phenomena in which the Fv/Fm value of both Symbiodiniaceae was immediately reduced. Transcriptome analysis of corals revealed that genes involved in the following processes were detected: endoplasmic reticulum stress, mitophagy, apoptosis, endocytosis, metabolic processes (acetyl-CoA, chitin metabolic processes, etc.), and the PI3K-AKT pathway were upregulated, while DNA replication and the calcium signaling pathway were downregulated in both C-and D-coral. These results suggest that unrepaired DNA- and protein-damages were accumulated in bleaching corals. Additionally, some DEGs were specific to C-coral or D-coral, including genes involved in TRP channels and vitamin B metabolic processes. Algal transcriptome analysis showed that increased expression of gene encoding photosystem and molecular chaperone especially in D-type symbiont. The transcriptome data implying a possible difference in the stress reactions on C-type and D-type symbiont. The results reveal the basic process of coral bleaching and symbiont-type-specific coral transcriptional responses, providing a perspective on the mechanisms that cause differences in coral stress tolerance.